Analisis Mutu Pelayanan Makanan untuk Event Wedding dengan Perbedaan Skala pada Katering X - Setyoningrum, Prastiwi Dwi; Sulandari, Lilis (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The catering industry, particularly wedding catering services, faces increasingly high demands for service quality as guest expectations and the complexity of event organisation rise. This study aims to analyse the quality of food service at wedding catering event X based on four aspects, namely food quality, service quality, presentation quality, and operational quality, and to compare these across three different event scales, namely 600, 3,000, and 5,000 guests. The study employs a qualitative descriptive approach with data collection techniques including in-depth interviews, observation, and document analysis. The research sample comprised ten participants selected through purposive sampling until data saturation was achieved, consisting of six invited guests, two banquet captains, one senior waiter, and one operations manager. Data analysis was conducted thematically to identify patterns of service quality across each event scale. The results of the study indicate that the quality of food presentation and food hygiene were relatively consistent and rated as good across all event scales. However, at larger event scales, a decline was observed in portion adequacy, the proactiveness of food refills, and the handling of guests with special needs. These findings suggest that an increase in event scale necessitates the strengthening of operational aspects to ensure service quality is maintained at an optimal level.